PENINGKATAN KEMAMPUAN MENULIS CERPEN MELALUI MODEL RANCANG BANGUN PADA PESERTA DIDIK KELAS IX A SMPN I TANJUNG - SUHENDRO SUHENDRO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The purpose of this study was to find out about increasing students' learning motivation in the application of the design model and to find out the improvement in learning outcomes of Indonesian language subjects, especially in short story writing material. In this study, two data collection techniques were used, namely the performance test technique and the observation technique. To analyze the data, the results of performance tests and observations were analyzed by comparative description, namely comparing the initial conditions, cycle I, cycle II. The procedure of classroom action research (CAR) which consists of 2 (two) cycles. In the first cycle, discussions with independent work consisting of 4-5 students are presented and responded to by other groups. In cycle II, the results of group work discussions were presented in front of the class and other groups responded. The results showed that there was an increase in the ability to write short stories from an average initial condition of 69.30, after the first cycle of actions was carried out an average of 74.30, to 88.4 at the end of cycle II. By applying the design model, the teacher in the learning process is more creative and applicable. ABSTRAKTujuan penelitian ini untuk mengetahui tentang peningkatan motivasi belajar peserta didik dalam penerapan model rancang bangun dan serta mengetahui peningkatkan hasil belajar mapel bahasa Indonesia terutama pada materi menulis cerpen. Dalam penelitian ini menggunakan dua teknik pengumpulan data yaitu dengan teknik tes unjuk kerja dan teknik observasi. Untuk menganalisis data, hasil tes unjuk kerja dan observasi dianalisis dengan deskripsi komperatif, yaitu membandingkan kondisi awal, siklus I, siklus II. Prosedur penelitian penelitian tindakan kelas (PTK) yang terdiri dari 2 (dua ) siklus.Pada siklus I diskusi dengan kerja mandiri yang terdiri dari 4-5peserta didik dipresentasikan dan ditanggapi oleh kelompok yang lain. Pada siklus II hasil diskusi kerja kelompok dipresentasikan di depan kelas dan ditanggapi oleh kelompok yang lain.Hasil penelitian dapat diketahui bahwa terjadi peningkatan kemampuan menulis cerpen dari kondisi awal rata-rata 69,30, setelah dilaksanakan tindakan siklus I rata-rata 74,30 ,menjadi 88,4 pada akhir siklus II.Penerapan model rancang bangun, guru dalam proses pembelajaran lebih kreatif dan aplikatif.